(untitled) (Annals of Medical Research, 2021)
Aim: Purpose of this study is to assess patients diagnosed with psychogenic hearing loss, who describe hearing deficiency complaints but lack the auditory pathology in audiological examinations, in terms of depression and anxiety levels. Psychogenic hearing loss is presence of hearing deficiency despite the absence of any pathology that could cause hearing loss in auditory system. Purpose of this study is to assess patients diagnosed with psychogenic hearing loss, who describe hearing deficiency complaints but lack the auditory pathology in audiological examinations, in terms of depression and anxiety levels. Material and Methods: In our study 54 female patients, who admitted to our clinic between July 2015 and June 2017 with solely hearing deficiency complaint and had no other complaints including mainly otorhinolaryngology and psychiatric diseases, and 51 healthy female subjects who volunteered to attend our study were compared with regards to their Beck Anxiety and Depression scores.Results: Comparison of mean ages of patients group included in the study and the control group did not reveal any statistically significant difference (p>0.05). No significant difference was observed among groups for both pure tone audiometry and speech sound differentiation scores (p>0.05). Beck Anxiety Scale and Beck Depression Scale scores of the patient group was determined to be statistically significantly greater than that of those control group (p0.001).Conclusion: Psychogenic hearing losses are examined as one of the pseudoneurologic symptoms observed in conversion disorder. Our study results show that women who admit with psychogenic hearing loss had higher depression and anxiety levels than healthy control subject, therefore, points to the necessity for these patients to be evaluated for anxiety and depression and followed up jointly by psychiatry department with regards to psychotherapeutic intervention needs.